Evaluation of the Chemical Composition of three Bottled Drinking Water Brands from Gaser Bin Gasheer, Libya, in Comparison with WHO and Libyan Standards (مجلة العلوم الشاملة, 2025)
Bottled water is an important source of drinking water in many developed and developing countries,including Libya. One of the main public health concerns related to bottled water consumption is itslow mineral content or the absence of essential minerals that are vital for human health. This studyaimed to assess the chemical quality of selected bottled water brands available in Bin Ghasheer,Libya) Uno , Aquasila, Sultan). A range of water quality parameters was analyzed, including physicalparameters (total dissolved solids (TDS)) and chemical parameters (calcium (Ca²⁺), and sulphate(SO₄²⁻)), using standard analytical procedures and compared with the standards set by the Libyanauthorities as well as the World Health Organization (WHO) guideline. "The results revealedsignificant variations among the tested bottled water samples and identified certain inconsistencies inthe information provided on the labels, emphasizing the need to strengthen regulatory oversight toensure the accuracy and reliability of information available to consumer.